Combination of Serum miRNAs with Serum Exosomal miRNAs in Early Diagnosis for Non-Small-Cell Lung Cancer - Wu Q; Yu L; Lin X; Zheng Q; Zhang S; Chen D; Pan X; Huang Y (Cancer Management and Research, 2020)
Qingwei Wu, 1, 2 Lili Yu, 1, 2 Xiaoqing Lin, 1, 2 Qingzhu Zheng, 1, 2 Songgao Zhang, 1, 2 Dunyan Chen, 1, 2 Xiaojie Pan, 1, 3 Yi Huang 1, 2, 4  1Provincial Clinical College, Fujian Medical University, Fuzhou 350001, People’s Republic of China; 2Department of Clinical Laboratory, Fujian Provincial Hospital, Fuzhou 350001, People’s Republic of China; 3Department of Thoracic Surgery, Fujian Provincial Hospital, Fuzhou 350001, People’s Republic of China; 4Center for Experimental Research in Clinical Medicine, Fujian Provincial Hospital, Fuzhou 350001, People’s Republic of ChinaCorrespondence: Yi HuangDepartment of Clinical Laboratory, Fujian Provincial Hospital, Fuzhou 350001, People’s Republic of ChinaEmail hyi8070@126.comPurpose: Circulating microRNAs (miRNAs) have shown the potential for non-invasive diagnosis of various types of malignancies at an early stage. The aim of the study was to explore the feasibility of a combination of 8 serum miRNAs related to non-small-cell lung cancer (NSCLC) with the corresponding serum exosomal miRNAs in early diagnosis for the patients with NSCLC.Methods: We measured 8 serum miRNAs and the corresponding serum exosomal miRNAs including miR-21-5p, miR-126-3p, miR-141-3p, miR-146a-5p, miR-155-5p, miR-222-3p, miR-223-3p, and miR-486-5p in 48 patients with early NSCLC at stages I/II, 32 patients with lung benign lesion (LBL), and 48 healthy control (HC) by quantitative real-time polymerase chain reaction (qRT-PCR).Results: The expression levels of 4 serum miRNAs including miR-21-5p, miR-141-3p, miR-222-3p, and miR-486-5p, and 2 serum exosomal miRNAs including miR-146a-5p and miR-486-5p in the early NSCLC group were significantly different from that in the LBL group and the HC group (P < 0.01). The areas under the receiver operating characteristic curves (AUC) of the 4 serum miRNAs and 2 serum exosomal miRNAs in the early NSCLC group were ≥ 0.697, of which serum exosomal miR-146a-5p and miR-486-5p were 0.813 and 0.886, respectively, and higher than that of the 4 serum miRNAs. Additionally, a combination of 4 serum miRNAs with 2 serum exosomal miRNAs improved the AUC to 0.960 for the patients with NSCLC at early stages, with a sensitivity of 85.42% and a specificity of 92.50%.Conclusion: This study suggests that serum exosomal miRNAs other than serum miRNAs might be preferable biomarkers for the patients with NSCLC at early stages, and a combination of serum miRNAs with serum exosomal miRNAs contributes to the further improvement of early diagnosis for NSCLC.Keywords: serum, exosome, microRNA, non-small-cell lung cancer, early diagnosis